2021
DOI: 10.1155/2021/6668990
|View full text |Cite
|
Sign up to set email alerts
|

Zingiberis Rhizoma Recens: A Review of Its Traditional Uses, Phytochemistry, Pharmacology, and Toxicology

Abstract: Zingiberis Rhizoma Recens (ZRR, the fresh rhizoma of Zingiber officinale Roscoe) is a widely used traditional Chinese medicine (TCM). It is also a traditional spice, widely used around the world. The present paper reviews advances in research relating to the botany, ethnopharmacology, phytochemistry, pharmacology, and toxicology of Zingiberis Rhizoma Recens. In addition, this review also discusses some significant issues and the potential direction of future research on Zingiberis Rhizoma Recens. More than 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 55 publications
0
25
0
2
Order By: Relevance
“…According to Compendium of Materia Medica , Zingiberis Rhizoma Recens can promote the generation of new tissues. Plenty of studies revealed that gingerols, essential oils, and diarylheptanoids were the major components of Zingiberis Rhizoma Recens and Zingiberis Rhizoma Recens showed excellent antioxidant, antibacterial, antitumor, and antiinflammatory activities ( Li et al, 2021 ). In the acetic acid-induced gastric ulcer rat model, orally administration of Zingiberis Rhizoma Recens aqueous extract (1.25, 2.5, and 5 g/kg) reduced the gastric ulcer area in dose-dependent manner via inhibiting the expression of the chemokines and TNF-α ( Ko and Leung, 2010 ).…”
Section: Botanical Drugs In Traditional Chinese Medicine With Wound H...mentioning
confidence: 99%
“…According to Compendium of Materia Medica , Zingiberis Rhizoma Recens can promote the generation of new tissues. Plenty of studies revealed that gingerols, essential oils, and diarylheptanoids were the major components of Zingiberis Rhizoma Recens and Zingiberis Rhizoma Recens showed excellent antioxidant, antibacterial, antitumor, and antiinflammatory activities ( Li et al, 2021 ). In the acetic acid-induced gastric ulcer rat model, orally administration of Zingiberis Rhizoma Recens aqueous extract (1.25, 2.5, and 5 g/kg) reduced the gastric ulcer area in dose-dependent manner via inhibiting the expression of the chemokines and TNF-α ( Ko and Leung, 2010 ).…”
Section: Botanical Drugs In Traditional Chinese Medicine With Wound H...mentioning
confidence: 99%
“…The rhizome of Zingiber officinale (Ginger) is used as a delicacy or spice, and it is also widely used in medicine. It belongs to family Zingiberaceae ( Li et al, 2021 ). One advantage of employing natural extracts like ginger is that it reduces the possibility of developing resistance; also, the residues of such natural items in meat are safe for human consumption and have no negative health consequences.…”
Section: Introductionmentioning
confidence: 99%
“…A partir da revisão sistemática acerca das plantas medicinais no âmbito da toxicologia clínica, os dados foram compilados no Quadro 1, que representa os elementos fundamentais de interesse deste estudo, a saber: 1) nome (popular e científico) das plantas medicinais encontradas nos suplementos alimentares objeto de análise deste trabalho; 2) ocorrência destas plantas nas listas oficiais de plantas medicinais brasileiras (RENAME, RENISUS ou Memento Fitoterápico); 3) informações referentes à toxicidade dessas plantas; e 4) referências científicas que relatam os possíveis efeitos tóxicos (BRASIL, 2009(BRASIL, , 2016(BRASIL, , 2020. (ALBANO et al, 2013;AMENI et al, 2015;BRASIL, 2010;BUENO et al, 2021;DE CAMPOS et al, 2015;FERREIRA et al, 2011;SPÓSITO et al, 2019) Espinheira Santa (AHMED et al, 2018;BRASIL, 2010BRASIL, , 2016DENG et al, 2019;KATO et al, 2006;LI et al, 2021 Esta pesquisa serve de alerta aos profissionais de saúde, especialmente, nutricionistas, médicos, farmacêuticos e outros profissionais prescritores de suplementos e plantas medicinais, sobre a necessidade de investigar e orientar o uso racional pela população, podendo ser usado para futuras ações de educação em saúde e como norteador para pesquisas futuras mais abrangentes, as quais devem preencher lacunas existentes.…”
Section: Resultsunclassified